DAYA HAMBAT GETAH TANAMAN JARAK TINTIR (Jatropha Multifida Linn) TERHADAP PROSES PENYEMBUHAN LUKA DI TINJAU DARI HASIL PEMERIKSAAN CLOTTING TIME - Siti Zaetun (poltekkes kemenkes mataram, 2014)
Abstract: One of the herbs that can help in healing this wound is Jatropha (Jatropha multifida Linn). Jatropha sap is often used as an adjuvant in the treatment of injuries to the outside of the skin (Anonymous, 2010). The purpose of this study was to determine how different the results of blood clotting time with and without the addition of plant sap tintir Jatropha (Jatropha multifida Linn)